Does Leisure Involvement Impact on Service Performance? Empirical Finding from the Indonesian Culinary Industry - Olivia Sri Kartika; Zurinawati Mohi Mohyi (Politeknik Negeri Bandung, 2019)
Many studies have examined the frontline service staff performance of various industries but rarely found to be associated with leisure involvement in the culinary industry. This study discusses the relationship between leisure involvement and service performance with mediation of variables subjective to well-being and job satisfaction. The research model used is PLS or partial least squares modelling, by taking samples from the frontline staff of culinary industry which amounts to 313 samples in Bandung City, Indonesia. The results of this study show that there is a significant relationship between leisure involvement and service performance, as well as with the mediator. In conclusion, an employee who is often involved in leisure activities is likely to be happy and will result in his good performance in serving customers. This is also influenced by his satisfaction in work, although the results are not too significant. The implication is that the management and businessmen need to pay greater attention to the welfare of employees should they wish to improve the service performance of their restaurants. This report is structured to meet one of the conditions for completing education.